Comparative accuracy of cardiovascular risk prediction methods in primary care patients. Issue 1 (1st January 2001) - Jones, A F; Walker, J; Jewkes, C; Game, F L; Bartlett, W A; Marshall, T; Bayly, G R
Abstract : OBJECTIVE: To compare the relative accuracy of cardiovascular disease risk prediction methods based on equations derived from the Framingham heart study. DESIGN: Risk factor data were collected prospectively from subjects being evaluated by their primary care physicians for prevention of cardiovascular disease. Projected cardiovascular risks were calculated for each patient with the Framingham equations, and also estimated from the risk tables and charts based on the same equations. SETTING: 12 primary care practices (46 doctors) in Birmingham. PATIENTS: 691 subjects aged 30–70 years. MAIN OUTCOME MEASURES: Sensitivity, specificity, and positive and negative predictive values of the Framingham based risk tables and charts for treatment thresholds based on projected cardiovascular disease or coronary heart disease risk. RESULTS: 59 subjects (8.5%) had projected 10 year coronary heart disease risks ⩾ 30%, and 291 (42.1%) had risks ⩾ 15%. At equivalent projected risk levels (10 year coronary heart disease ⩾ 30% and five year cardiovascular disease ⩾ 20%), the original Sheffield tables and those from New Zealand have the same sensitivities (40.0%, 95% confidence interval (CI) 26.6% to 57.8% v 41.2%, 95% CI 28.7% to 57.3%) and specificities (98.6%, 95% CI 97.2% to 99.3% v 99.7%, 95% CI 98.8% to 100%). Modifications to the Sheffield tables improve sensitivity (91.4%, 95% CI 81.3% to 96.9%) but reduce specificity (95.8%, 95% CI 93.9% to 97.3%). The revised joint British recommendations' charts have high specificity (98.7%, 95% CI 97.5% to 99.5%) and good sensitivity (84.7%, 95% CI 71.0% to 93.0%). CONCLUSIONS: The revised joint British recommendations charts appear to have the best combination of sensitivity and specificity for use in primary care patients.